Case report: Deterioration of infantile hemangioma related to oral or nebulized administration of β2-AR agonist: Three cases reports - Chen, Qiang; Zhang, Yunxuan; Sun, Chenyu; Liu, Li; Luo, Xiaoyan; Wang, Hua; Ni, Sili (Frontiers in Oncology, 2022)
Infantile hemangioma (IH) is a benign vascular tumor, presenting a unique sequence of nonlinear growth and spontaneous involution. Some hemangiomas require opportune treatment to avoid functional and aesthetic insufficiency. Although systemic β2-adrenergic receptor (β2-AR) antagonists have been increasingly used as the first-line treatment since 2008, the IH rebound still exists with uncertain mechanism. Here, we report three cases of abrupt IH deteriorations that are mainly related to β2-AR agonists administration. Potential IH proliferation induced by β2-AR agonists, especially from oral or nebulized approaches, should be recognized more widely by healthcare providers. Additionally, it is necessary to carry out large sample studies to analyze the influence of β2-AR agonist administration on the deterioration of IH.